Learning Legacies: Archive to Action through Women's Cross-Cultural Teaching Learning Legacies - Sarah Ruffing Robbins (Digital Culture Books: The New Public Scholarship, 2017)
Learning Legacies explores the history of cross-cultural teaching approaches, to highlight how women writer-educators used stories about their collaborations to promote community-building. Robbins demonstrates how educators used stories that resisted dominant conventions and expectations about learners to navigate cultural differences. Using case studies of educational initiatives on behalf of African American women, Native American children, and the urban poor, Learning Legacies promotes the importance of knowledge grounded in the histories and cultures of the many racial and ethnic groups that have always comprised America's populace, underscoring the value of rich cultural knowledge in pedagogy by illustrating how creative teachers still draw on these learning legacies today.